An Analytical Study of Solvency, Liquidity and Bottom Line, of Listed Indian Automobile Companies - Lieutenant Dr. Yashodhan P Mahajan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Sustaining concord among bottom line (Net Profitability), solvency and liquidity is acutely necessary for stable and holistic growth and development of every business. Liquidity, Profitability and Solvency (LPS) of every business is significantly afflicted through internal & external environmental factors such as economic fluctuations, ups and downs in business cycle, product life cycle, and pandemic situations of so and so forth. Continuing business, facing all above-mentioned conditions is a herculean task for each business. Marinating sustainable and holistic growth through attuning Liquidity, Profitability and Solvency (LPS) required systematic, professional and ethical approach pursued by management of the business. The basic objective behind this study is to analyze Liquidity, Profitability and Solvency (LPS) of selected automobile companies in India. It can be analyzed by evaluating the various ratios like profitability, liquidity and solvency. For this research study five years data viz. (2015 – 2020) of four giant companies were considered in automobile sector i.e., Maruti Suzuki, Hyundai India, Tata Motors Ltd and Mahindra & Mahindra Ltd. Researcher tried to find out correlation among liquidity, profitability, and solvency. Researcher found that that there is strong significant negative relationship between liquidity profitability and solvency.